Productive Behavior of Pigs Fed with Pelled Feed Plus the Addition of a Microbial Preparation - L Mariño-Salazar; J Usca-Méndez; L Tello-Flores; L Flores-Mancheno (ESPOCH Congresses, 2023)
Abstract This study aimed to assess the performance of pigs in terms of productivity when they were given pelleted feed along with microbial preparations at Paty Pig Farm in Yaruquies parish, Riobamba Canton, Chimborazo province. The duration of the study was 90 days and included 48 piglets of Yorkshire x Landrace crossbreed. These piglets were weaned at 21 days of age and weighed an average of 6.5 kg, with 24 males and 24 females. The study used three different levels (2%, 4%, and 6%) of microbial preparation in comparison to a control group. A completely randomized design (DCA) was used in combination with two factors: prebiotic addition (factor A) and animal gender (factor B). The productive behavior of pigs showed no significant differences in the parameters such as feed intake, total feed intake, and feed conversión, among the groups. However, the final weight and weight gain showed better results in the groups that received microbial preparation. The study suggested that microbial preparation levels of 2%, 4%, and 6% can be used as it improved the final weight and weight gain by 37.57 kg and 30.70 kg, respectively, compared to the control group. No mortality was reported due to the use of microbial preparation. The study recommends the use of microbial preparation in other stages of pig production to verify its benefits.